Strategic Analysis of Cross-Border E-Commerce Platform Operations: A Case Study of Hefei Reying International Trade Co., Ltd. - Jing Bao (Studies in Social Science & Humanities, 2025)
This paper deeply analyzes the cross-border e-commerce platform operation strategy of Hefei Reying International Trade Co., Ltd., aiming to enhance its market competitiveness. First, the paper explores the company’s market positioning, clarifying its target market and competitive landscape. Next, it elaborates on the company’s strategy in e-commerce platform selection and customization, including the basis for platform selection and store design. The paper also focuses on the practice of digital marketing and brand building, such as search engine optimization, social media marketing, and email marketing. In addition, through case analysis, it demonstrates the specific measures and effect evaluation of the company in optimizing user experience. Finally, it summarizes the research results and proposes prospects and suggestions for future development.